All of us villains - Foody, Amanda; Herman, Christine Lynn (Tor Teen, 2021)
Every generation, seven families select a champion to compete in a tournament to the death for control of high magick--the most powerful resource in the world--but this year, a salacious tell-all book draws reporters, tourists, and government agents to Ilvernath to watch the bloody curse unfold and some of the champions are determined to thwart their destinies and rewrite their stories.